The Management System of Gedhang Godhog Arts Studio, Campurdarat District, Tulungagung Regency - Ninggar, Pungky Dara; Handayani, Enie Wahyuning (Solah, 2025)
This The Gedhang Godhog Art Studio is a place or place to gather and practice the arts, especially kentrung kreasi or kentrung theater. This studio was founded by Mr. Yayak Priasmara in 2011 with the aim of introducing the art of kentrung to young people, so he collaborated with theater. The author is interested in knowing how to manage the Gedhang Godhog art studio to survive and exist in the midst of the onslaught of foreign cultures. So in this study, the author formulates the problems (1) the management system applied in the Gedhang Godhog Art Studio (2) the supporting and inhibiting factors encountered in the Gedhang Godhog art studio. The research method is qualitative descriptive with a descriptive approach. Data collection techniques through observation, interviews and documentation. Data collection analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. Data validity using source triangulation, technique triangulation, and time triangulation. The results of the research and discussion show that the management system of the Gedhang Godhog art studio is managed very modestly, prioritizing family with communication or negotiations. The management system of the Gedhang Godhog art studio includes management elements consisting of 6 M's, namely man, money, methods, materials, machines and markets and the management functions applied include planning, organizing, mobilizing and supervising. If inhibiting factors are found, they will be discussed or discussed so that they can be resolved immediately. The conclusion of this study is that the management system of the Gedhang Godhog art studio has succeeded in achieving its goals by using a family system and always prioritizing deliberation or negotiation.